PENGARUH CITRA MEREK, INOVASI DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN TEH GELAS DI KOTA BATAM - SHERLY CHAIRANI; Nur Elfi Husda (SCIENTIA JOURNAL, 2025)
This study aims to analyze the influence of brand image, innovation, and advertising on the purchasing decision of Teh Gelas in Batam City. It also seeks to identify which of these factors plays the most dominant role in influencing consumer behavior. Furthermore, the study aims to provide insights into how marketing strategies can be optimized to attract and retain customers. The findings are expected to serve as a reference for businesses in the packaged beverage industry to strengthen their market positioning. Using a quantitative method with a descriptive approach, data was collected through an online questionnaire completed by 100 respondents. Data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests. The results indicate that brand image, innovation, and advertising have a significant influence on purchasing decisions both partially and simultaneously. Advertising has the most dominant influence, as indicated by the highest t-value compared to other variables. The findings imply that a more effective marketing strategy in enhancing brand image, product innovation, and advertising exposure can improve the competitiveness of Teh Gelas in the packaged beverage market.